A contribution to the taxonomy of the genus Rhaponticoides (Asteraceae, Cardueae) - Negaresh, Kazem (Phytotaxa, 2019)
A taxonomic synopsis of the genus Rhaponticoides is presented. Rhaponticoides kultiassovii, R. lasiopoda, R. phyllopoda, R. androssovii, R. gontscharovii, R. alaica, R. modesti, R. ruthenica var. bipinnatifida, R. sect. Vicentinae, R. sect. Africanae, R. sect. Turkestanicae and R. sect. Aralocaspicae are proposed as new combinations. Full description for R. sect. Vicentinae, R. sect. Africanae, R. sect. Turkestanicae and R. sect. Aralocaspicae and a key for all sections are presented for the first time here. My previous descriptions of R. sect. Iranicae and R. sect. Ruthenicae are revised. Two names, R. kultiassovii and R. lasiopoda, are typified. In addition, type details, full descriptions, morphological comparisons, distribution and habitat of transferred taxa are given. Finally, a new list of species of the genus Rhaponticoides with their heterotypic synonyms, geographical distributions and chromosome numbers is provided.